Intertidal: essaying the transcorporeal self - Fagan, Melissa (Curtin University, 2023)
This thesis is a manifestation of my attempt to create a series of transcorporeal essays. The essays emerge from, and exist within, the intertidal space between exegetical and creative, critical and performative, aesthetic and theoretical, self and place. This thesis performs and interrogates the ways in which surfing has helped nurture a life writing practice that is embodied and experiential, and become a way of being in, and bearing witness to, coastal environments and cultures.